Comparative energy and exergy analysis and optimisation study on the supercritical CO2recompression power cycle - Gumus, Emrah; Bashan, Veysi (INDERSCIENCE ENTERPRISES LTD, 2020)
The current study aims at optimisation and comparing the recuperative s-CO(2)cycle with the re-compression s-CO(2)cycle in case of changes in turbine and compressor isentropic efficiency and TITs. Below 317 degrees C the TIT recuperated Brayton cycle (RBC) has a higher cycle efficiency than RCBC for the case where compressor efficiency is 75% and turbine efficiency is 80%. RBCs with having higher turbomachinery efficiencies (eta(c)= 85%,eta(t)= 90%) have higher cycle thermal efficiency than RCBCs with lower turbomachinery efficiencies (eta(c)= 75%,eta(t)= 80%). These results will remedy the gap in the literature on information for selecting the appropriate cycle for various purposes under certain thermodynamic inlet conditions.
Keywords: recompression cycle; supercritical; s-CO2; carbondioxide; thermodynamic analysis; exergy analysis; CO2 RECOMPRESSION; POINT TEMPERATURE; PERFORMANCE; TURBINE; Thermodynamics; Energy & Fuels